Assessing Intellectual Capital Efficiency of Indian Banks: A Comparative Study of Public and Private Sector Banks - Gupta, Payal (International Journal of Engineering and Management Research, 2024)
The importance of Intellectual Capital has grown as knowledge-based, dynamic, and technologically upgraded businesses have expanded throughout the global world. Intellectual Capital is considered as a major asset for many organizations today. An optimum use of intellectual capital can add to competitive strength of an organization. Banking sector is regarded as a knowledge-intensive industry therefore it is crucial for banking industry to effectively utilize its intellectual capital so that value can be created. The current study aims to analyse the intellectual capital performance of Indian banks in general and make a comparative analysis of the variations in the intellectual capital performance among public and private sector banks in India in particular. Data has been gathered for Top 10 public and private sector banks according to market capitalization and analysed using Value Added Intellectual Capital Methodology developed by Pulic (1998) for a period of 5 years spanning from 2018-2022. The results of the study confirmed that a wide variation exists in intellectual capital performance among Indian banks. Private sector banks exhibited a better performance as compared to public sector banks.